Identificacion de peligros y evaluacion de riesgos según la norma ohsas 18001:2007 en el taller de cereales y leguminosas - Vásquez Urrunaga, Ivan Santos (2015)
In this research we identify the dangers and risk assessment of occupational safety and health based on the OHSAS 18001 at the “Taller de Cereales y Leguminosas” of the Agro-industrial Professional School of Engineering, Faculty of Agricultural Sciences of the National University of Trujillo. The methodology used for the preparation of the IPER was the Generalized Methodology, where the analysis applies to two determining factors: (a) Probability and (b) Severity. The result of this analysis determined that the most significant risks belong to the stages of: kneading, cutting the dough, baking, beaten and the adding of products.